Barriers to mental health services at public health centers: Providers’ perspectives - Putu Aryani; Pande Putu Januraga; Komang Ayu Kartika Sari; Lisanne Gerstel; Willem F Scholte (Public Health and Preventive Medicine Archive, 2019)
Background and purpose: The disparity between the increasing prevalence of mental health (MH) illness and the availability of treatment in Indonesia remains high, despite the campaign to provide MH services at public health centers (PHCs) initiated by the government in 2014. This study explored barriers to MH service provision at PHCs in Denpasar, Bali, Indonesia in order to identify priorities for service improvement. Methods: This explorative qualitative study was conducted from March to December 2015 and employed in-depth interviews and focus group discussions (FGDs). In-depth interviews were conducted with the Head of Denpasar City Health Office and with general practitioners (GPs) from four PHCs in Denpasar, to explore the perspective of policy and service management and experiences in PHC clinics, respectively. To further explore MH service implementation in the community, two FGDs were conducted with MH program managers and community health workers (CHWs). The interviews and FGDs were recorded, and verbatim transcripts were analyzed using thematic framework analysis. Results: Barriers to MH service provision identified in our study are poor dissemination of the national policy to the local government and PHCs; low prioritization of MH issues; organization workforce issues; funding concerns; poor coordination and supervision; poor management and recording system; scarcity of ancillary facilities and other resources such as psychotropic medicines. Conclusion: The findings of this study highlight the importance of national policy dissemination and collaboration between local government, health providers and CHWs to overcome the barriers in providing MH services at PHC level.